2017
DOI: 10.1016/j.siny.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal administration of prebiotics and probiotics

Abstract: SUMMARY Colonization of the neonatal gut by beneficial bacteria is important for the establishment and maintenance of the mucosal barrier, thus protecting the neonate from enteric pathogens and local and systemic inflammation. The neonatal microbiome is influenced by infant diet, environment, and the maternal microbiome. Dysbiosis in pregnancy increases the risk of pre-eclampsia, diabetes, infection, preterm labor, and later childhood atopy. Dysbiosis of the neonatal gut plays an important role in colic in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 60 publications
(61 reference statements)
1
41
0
2
Order By: Relevance
“…The gut microbiota is being increasingly implicated in the pathogenesis of NAFLD (59, 60). Here, our data provide supporting evidence for the role of both maternal diet and microbiota and lifelong dietary patterns on gut microbiota, as the gut microbial composition of offspring, based on maternal diet, differed most at 3 wk, followed by 11, and finally 24 wk (6163). These data are consistent with the current dogma that diet is a major driver of gut microbial composition (62), as there was a clear convergence in microbial abundances between offspring of different maternal groups as time on the HFS diet progressed.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The gut microbiota is being increasingly implicated in the pathogenesis of NAFLD (59, 60). Here, our data provide supporting evidence for the role of both maternal diet and microbiota and lifelong dietary patterns on gut microbiota, as the gut microbial composition of offspring, based on maternal diet, differed most at 3 wk, followed by 11, and finally 24 wk (6163). These data are consistent with the current dogma that diet is a major driver of gut microbial composition (62), as there was a clear convergence in microbial abundances between offspring of different maternal groups as time on the HFS diet progressed.…”
Section: Discussionsupporting
confidence: 74%
“…Finally, we provide evidence that hepatic steatosis is associated with alterations in metabolites associated with 1-carbon metabolism and insulin resistance, which were linked with abundance of specific gut microbial groups. Prebiotic supplementation represents a simple dietary means of improving metabolic health, and, although there are a limited number of clinical trials involving maternal prebiotic supplementation, it has been suggested as a safe and feasible method of improving maternal outcomes (63). The data presented here provide foundational long-term time-course evidence that maternal OFS supplementation may also improve the metabolic health of the offspring, in particular hepatic steatosis, in later life.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In vitro, L. plantarum is reported to protect the epithelial barrier disruption caused by enterotoxigenic Escherichia coli (ETEC) in intestinal porcine epithelial cells (Wang, Zeng, et al, ; Wu et al, ). The neonatal period is a critical time to establish a stable, lifelong host–microbial homeostasis; colonization by beneficial bacteria is important for maintaining the intestinal mucosal barrier and protecting the neonates from pathogens and inflammation (Sohn & Underwood, ; Stockinger, Hornef, & Chassin, ). However, the effect of L. plantarum on the gut health of suckling piglets is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, maintenance of the viability of probiotic bacteria in the food matrix has been a prerequisite for ensuring its effect on the host health (ZACARIAS et al, 2011). SOHN and UNDERWOOD (2017) pointed out that innovative methods of probiotic delivery should be explored since nowadays probiotic products are limited to the microorganism's resistance to the gastrointestinal stress.…”
Section: Health Benefits Of Functional Probiotic Prebiotic and Synbmentioning
confidence: 99%